2017
DOI: 10.4103/nah.nah_65_16
|View full text |Cite
|
Sign up to set email alerts
|

Headphone listening habits and hearing thresholds in swedish adolescents

Abstract: Introduction:The aim of this study was to investigate self-reported hearing and portable music listening habits, measured hearing function and music exposure levels in Swedish adolescents. The study was divided into two parts.Materials and Methods:The first part included 280 adolescents, who were 17 years of age and focused on self-reported data on subjective hearing problems and listening habits regarding portable music players. From this group, 50 adolescents volunteered to participate in Part II of the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 17 publications
2
35
0
5
Order By: Relevance
“…The prevalence was greater compared with a comprehensive US survey with the same methodology as ours (Shargorodsky, Curhan, Curhan, & Eavey, ) that examined 2,300 adolescents aged 12–19. The US study found mild or worse hearing loss among 5% of the study population, and results are considered to be generalisable to the US population (there are no comparable Swedish studies of ‘normal population’ adolescents; see Widén, Bålsjö, Möller, & Kähäri, ). Our sample is small but high rates of hearing problems among youth in secure residential units have been reported previously (e.g., Shelton, ).…”
Section: Discussionmentioning
confidence: 94%
“…The prevalence was greater compared with a comprehensive US survey with the same methodology as ours (Shargorodsky, Curhan, Curhan, & Eavey, ) that examined 2,300 adolescents aged 12–19. The US study found mild or worse hearing loss among 5% of the study population, and results are considered to be generalisable to the US population (there are no comparable Swedish studies of ‘normal population’ adolescents; see Widén, Bålsjö, Möller, & Kähäri, ). Our sample is small but high rates of hearing problems among youth in secure residential units have been reported previously (e.g., Shelton, ).…”
Section: Discussionmentioning
confidence: 94%
“…[10] The same rate was found as 90% in a study in Sweden. [2] Headphone use while resting was found as 56%, which was found as 60% and 25% in two other studies. [2,10] Use while studying was found as 42% and use while doing sports was 39%.…”
Section: Discussionmentioning
confidence: 60%
“…Another study found the presence of ear-related symptoms as 7%. [2] There was a positive correlation between this question and total scores (p<0.05). There was a negative correlation between results of this question and minimal anxiety score of 0-7 (p<0.05).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Listening to headphones while memorizing words triggered a mood-dependent effect that caused mental disruption, and therefore, a decrease in memory retention [8]. Women have been reported to be more subjective to hearing problems when compared with men but exhibited better hearing thresholds [9]. The present study aimed at investigating the possible adverse effects use of headphones caused to working memory in long term mobile headphones users.…”
Section: Introductionmentioning
confidence: 99%